Internuclear ophthalmoplegia – causes, symptoms and management - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Internuclear ophthalmoplegia (INO) is a disorder of eye movements caused by a lesion in an area of the brain called the medial longitudinal fasciculus (MLF). The most common causes of INO are multiple sclerosis and brainstem infarction. Other causes include head trauma, brainstem and fourth ventricular tumors, Arnold-Chiari malformation, infection, hydrocephalus, and lupus erythematosus. Internuclear ophthalmoplegia is clinically characterized by total or partial failure to adduct one eye in lateral gaze and a monocular nystagmus of the abducting eye. It may be unilateral and bilateral. The method of choice for diagnostic imaging of MLF lesion in patients with INO is magnetic resonance. In this article authors present current opinion about pathogenesis, clinical symptoms, and management in patients with internuclear ophthalmoplegia.